KOMITE AUDIT MEMODERASI HUBUNGAN ANTARA CSR DAN BOARD STRUCTURE TERHADAP MANAJEMEN LABA RIIL PADA PERUSAHAAN LQ45 - Sarah Widyana Putri (2023)
The purpose of this study is to examine the influence of the audit committee in moderating the relationship between CSR and board structure on real earnings management. The population used in this study are companies registered on LQ45 in the period 2018 to 2021. The samples obtained from this research were conducted using the purposive sampling method which produced 92 sample companies. Hypothesis testing was carried out using multiple linear regression analysis which showed that the CSR variable and the interaction variable from the Audit Committee and the Board of Independence had a significant relationship to real earnings management. Meanwhile, board size and board independence as well as audit committee moderation with CSR and board size have no effect on real earnings management. The use of the control variable, namely profitability, has no effect on real earnings management.